1972
DOI: 10.1126/science.176.4039.1149
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Induction: Perceptual Synthesis of Absent Sounds

Abstract: Within certain auditory patterns, fainter sounds may be "heard" clearly when replaced by louder sounds having appropriate spectral compositions. This auditory induction of fainter by louder sounds can cancel the perceptual effects of masking. Phonemic restorations, which have been reported previously, appear to be a specialized application to speech of the much broader phenomenon of auditory induction. The rules governing auditory induction indicate that it helps maintain stable auditory perception in our freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
177
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 7 publications
14
177
2
Order By: Relevance
“…However, reduction of the loudness of the inducer also occurred (to a lesser extent) when the inducee appeared to be discontinuous. This observation appears to conflict with the assumption made in studies reported by Houtgast (1972), Warren et al (1972), and others that restoration is an all-or-none phenomenon, as is indeed the case when it is measured as the continuity/discontinuity transition or "pulsation threshold" of the inducee (see Warren, 1984, for a review of this literature).…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…However, reduction of the loudness of the inducer also occurred (to a lesser extent) when the inducee appeared to be discontinuous. This observation appears to conflict with the assumption made in studies reported by Houtgast (1972), Warren et al (1972), and others that restoration is an all-or-none phenomenon, as is indeed the case when it is measured as the continuity/discontinuity transition or "pulsation threshold" of the inducee (see Warren, 1984, for a review of this literature).…”
contrasting
confidence: 45%
“…These studies have generally concentrated on apparent continuity of the inducee and have neglected to examine possible concomitant changes in the inducer. Although it has been suggested that a portion of the neural response to the inducer is subtracted and used for the perceptual synthesis of the inducee (Warren, Obusek, & Ackroff, 1972), direct experimental data supporting this hypothesis is lacking. The series of experiments described here examine consequences of the hypothesis that restoration is based on a reciprocal interaction involving the allocation of a portion of the auditory input produced by the inducer over to the inducee.…”
mentioning
confidence: 99%
“…Many natural sounds such as speech are spectro-temporally sparse, so energetic masking often affects only portions of the target, limited in both time and frequency [31]. Moreover, we perceptually fill in inaudible portions based on glimpses we hear (see Text Box 2) [32,33,34]. As a result, energetic masking is often not the main factor limiting performance.…”
Section: Energetic Maskingmentioning
confidence: 99%
“…Over the last few decades, the continuity illusion has been extensively studied in behavioral experiments using a variety of stimuli, including pure and modulated tones, tone glides, and speech (Carlyon, Micheyl, Deeks, & Moore, 2002;Warren, Wrightson, & Puretz, 1988;Ciocca & Bregman, 1987;Powers & Wilcox, 1977;Houtgast, 1972;Warren, Obusek, & Ackroff, 1972;Vicario, 1960;Miller & Licklider, 1950). The results of all these studies have led to a firm understanding of the stimulus parameters that do and do not lead to a percept of illusory continuity.…”
Section: Introductionmentioning
confidence: 99%